Beta-carotent and Antioxidant Activity of Starfruit Extract Powder (Avverhoa blimbi L) - Taufiq, Nuramaniyah; Mus, Rosdiana; Palimbong, Deske (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2021)
Wuluh starfruit is as a tropical plant that has sour taste but it has high nutritional value. One of wuluh starfruiut antioxidant contents is β-carotene. This research aimed to know β-carotene and test of antioxidant activity on Wuluh starfruit. Method of reseach was observational conducted at Chemistry Laboratory of Ujung Pandang Polytechnic with poject of quantitative test using spectrophotometry UV-Vis. The length of wave (nm) was 480 with 0,066 ABS (Absorban) value to analyze β-carotene level and antioxidant test (IC50) with wave length (nm) of 517. Concentration varian used were 0,1 %, 0,2 %, 04 % dan 0,8 % using spectrophotometry UV-Vis with DPPH solution reagent (1,1-dhipenyl-2-picryhirdazyl). This research indicated that quantitative test using spectrophotometry UV-Vis was obtained 24,99555 ppm β-carotene level and the result of antioxidant test (IC50) to reduce 50 % free radicals in DPPH solution required a dry powder sample contentration of 0,6 %.